Comparative study of antidiabetic activity of Cajanus cajan and Tamarindus indica in alloxan-induced diabetic mice with a reference to in vitro antioxidant activity - Nahar, Laizuman; Haque, Ekramul; Nasrin, Fatema; Mosaddik, Ashik; Zahan, Ronok; Haque, Anamul (© 2014 Pharmacognosy Network Worldwide, 2016)
This article was published in Pharmacognosy Research [© 2014 Pharmacognosy Network Worldwide] and the definite version is available at: http: http://www.phcogres.com/article.asp?issn=0974-8490;year=2014;volume=6;issue=2;spage=180;epage=187;aulast=Nahar The article website is at: http://www.phcogres.com